A Longitudinal Assessment of Outcomes and Healthcare Resource Utilization After Immediate Breast Reconstruction—Comparing Implant- and Autologous-based Breast Reconstruction. Issue 4 (October 2015) - Fischer, John P.; Fox, Justin P.; Nelson, Jonas A.; Kovach, Stephen J.; Serletti, Joseph M.
<x xml:space="preserve">Abstract</x> Objectives: Immediate breast reconstruction (IBR) after mastectomy for cancer has increased in recent years, yet long-term, modality-specific comparative data are lacking. We performed this study to compare short- and long-term outcomes after expander, autologous (AT), and direct-to-implant (DI) breast reconstruction. Methods: Using four state-level inpatient and ambulatory surgery databases, we conducted a retrospective cohort study of adult women who underwent mastectomy with immediate breast reconstruction from 2008 to 2009. Our primary outcomes were complications within 90 days of surgery, rate of secondary breast surgery within 3 years, and cumulative healthcare charges. Results: The final cohort included 15, 154 women who underwent mastectomy with tissue expander (TE: 70.5%), autologous (AT: 18.1%), or direct to implant (DI: 11.3%) reconstruction. Ninety-day complications were lowest after expander and highest after AT breast reconstruction (TE = 6.5% [reference] vs AT = 13.1% [2.09, 1.82–2.41] vs DI = 6.6% [1.03, 0.84–1.27], P < 0.001). However, adjusted rates of secondary breast procedures were most frequent after expander (2021/1000 discharges) and least frequent after AT (949.0/1000 discharges) reconstruction (P < 0.001). Specifically, unplanned revisions were highest among the tissue expander cohort (TE = 59.2% vs AT = 34.4% vs DI = 45.9%, P < 0.001). The cumulative, adjusted healthcare charges for secondary breast procedures differed slightly across groups (TE = $63, 806 vs AT = $66, 882 vs DI = $64, 145, P < 0.001). Conclusions: Complications and secondary breast procedures, including unplanned revisions, after breast reconstruction are common and vary by reconstructive modality. The frequency of these secondary procedures adds substantial healthcare charges to the care of the breast reconstruction patient.